(untitled) (Medico Legal Update, 2020)
This study was reflected on the correlations between the polycystic ovary syndrome (PCOS) and a Single Nucleotide Polymorphism (SNP) T45G in the adiponectin gene among Iraqi infertile women with polycystic ovary syndrome. Eighty primary infertile women with PCOS, sixty-two secondary infertile women with PCOS and 50 healthy fertile women in Iraq were included in this study, Blood samples were collected from the infertility clinic in Azadi Teaching Hospital and AL-Salam Hospital. The age of infertile and fertile women was ranged from 18 to 46 years. Results showed association between T45G polymorphism in the adiponectin gene and infertile PCOS women. Moreover, infertile women with PCOS with these polymorphisms have been reported to have higher LH, FSH and prolactin concentrations and BMI. In conclusion 45T?G polymorphisms have been shown to be associated with an increased risk of PCOS women with PCOS with these polymorphisms have been reported to have higher LH, FSH and prolactin concentrations and BMI